The effects of positive visualization with and without sound on sleep actigraphy measures in a small sample of tinnitus patients - Spittal, Jackie; Warman, Guy; Durai, Mithila; Searchfield, Grant D. (Frontiers in Audiology and Otology, 2024)
Background. Tinnitus is a common oto-neurological disorder associated with sleep disturbance. This research explored visualization and visualization reinforced with nature sounds as an acute therapy for sleep disturbance in persons with tinnitus. Methods. Twelve adults with bothersome tinnitus and sleep disturbances participated in a randomized cross-over design in which measurements of tinnitus perception (rating scales) anxiety/depression (Hospital Anxiety and Depression Scale) attention (Attention and Performance Self-Assessment) and sleep quality (sleep diary and actigraphy (automated estimates of total sleep time, sleep onset latency, sleep fragmentation, and wake after sleep onset) were undertaken at a baseline and repeated with therapy. The visualization task was thirty minutes in duration and was performed every night before sleep, the visualization with sound reinforcement task added nature sounds played overnight. Results. Sleep onset latency analyzed using the sleep diary normalized actigraphy was significantly reduced with both interventions (visualization reduced by 60 mins, visualization with sound reinforcement reduced by 70 mins). None of the other sleep quality markers demonstrated statistically significant change. Self-reported attention ability significantly improved with visualization. Of participants 90% were able to consistently complete actigraphy measures over the 3 weeks of the study and 75% sleep diaries. Conclusions. Sleep onset time reduced with visualization.